(untitled) (Economics and region, 2022)
The questions of assessment of the process of formation and support of the image of innovative enterprise as a factor of its competitiveness in the context of new challenges and threats are actualized. It is noted that the image of domestic enterprises influenced the ratings of global and digital competitiveness of Ukraine in 2015–2019. The concept of image, brand and reputation of the enterprise is distinguished. Based on the study of literary sources formed the author’s definition of the category "image of an innovative enterprise" as the internal and external appearance of the enterprise, which significantly affects its competitiveness through the implementation of innovative activities, and is a significant factor in improving its level in the face of growing challenges and threats. The analysis of the authors’ approaches to the assessment of the process of formation and support of the enterprise image allowed to highlight the most significant indicators and criteria for its assessment as a factor of enterprise competitiveness, namely: business image (transparency of business activity, loyalty to clients, partners’ impression of the company, reliability, openness of data on sales volumes, market share, range of goods, price flexibility); social image (sponsorship, charity, support of social movements, participation in solving environmental problems, employment, health care, and so forth), etc.